Children’s reading tendencies and their relationship to age stages) animal stories as an example) (Journal of the College of Basic Education, 2024)
In our research, we discussed children’s reading tendencies, phases, and age stages towards these stories, especially animal stories, because they contain attractive images and shapes of animals, and they are usually close to humans, especially the child. He loves them, gets close to them, and memorizes their names and shapes. These stories usually carry social, humanitarian, scientific, religious, and historical implications. On the tongue of animals. This is a good and useful method because through it ideas, sermons, and wisdom are conveyed to the child .